2007
DOI: 10.1177/0022002706296155
|View full text |Cite
|
Sign up to set email alerts
|

Rational Terrorists and Optimal Network Structure

Abstract: After the events of 9/11, U.S. counterterrorism became more proactive in that the Patriot Act allowed the authorities far more freedom to directly attack terrorist network structures. We argue that rational terrorists will attempt to thwart such policies and restructure themselves to be less penetrable. We model the trade-off between security and intragroup communication faced by terrorists. The model is used to derive the anticipated changes in network structure and the consequent changes in the type, complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 12 publications
0
69
0
1
Order By: Relevance
“…Additionally, Arquilla and Ronfeldt (2001) suggested that other hybrid structures may be feasible. While recent efforts have been made to model the most appropriate structure (see Enders and Su 2007;Lindelauf, Borm, and Hamers 2009), we know of no other data set that comprehensively captures data on the core membership of a terrorist organization and analyzes the structures actually formed among the members. This paper attempts to fill that gap.…”
Section: Abstract Conflict Network Analysis Terrorismmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Arquilla and Ronfeldt (2001) suggested that other hybrid structures may be feasible. While recent efforts have been made to model the most appropriate structure (see Enders and Su 2007;Lindelauf, Borm, and Hamers 2009), we know of no other data set that comprehensively captures data on the core membership of a terrorist organization and analyzes the structures actually formed among the members. This paper attempts to fill that gap.…”
Section: Abstract Conflict Network Analysis Terrorismmentioning
confidence: 99%
“…We will return to the question of IED activity throughout this paper, as our data was constructed to aide in the study of PIRA's use of IEDs, which long predated the popular familiarity with the term during the U.S. occupation of Iraq (Gill, Horgan, and Lovelace 2011). Enders and Su (2007) and Lindelauf, Borm, and Hamers (2009) suggest that structural changes in terrorist groups may reflect changes in counterterrorism tactics. To account for this, we present analyses from four distinct "phases" of the Northern Irish conflict that correspond to key changes in PIRA's strategy and tactics.…”
Section: Abstract Conflict Network Analysis Terrorismmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies of bright networks have lent empirical support for this conclusion and suggest that a curvilinear relationship exists between the ideal mix of ties and network effectiveness across a spectrum of contexts, including the risk of an individual committing suicide, the success of Broadway musicals, and the abilities of firms and companies to perform in the market successfully (Pescosolido & Georgianna, 1989;Uzzi, 1996Uzzi, , 2008Uzzi & Spiro, 2005). Similarly, an increasing number of dark network studies have found that they too cannot be too provincial or cosmopolitan although it is typically discussed through the prism of balancing operational capacity and network (Bakker, Raab, & Milward, 2011;Bienenstock & Bonacich, 2003;Enders & Su, 2007;Milward & Raab, 2006). What constitutes a particular dark network's optimum balance will also vary depending on the environment in which it operates (e.g.…”
Section: Network Topography: Cohesionmentioning
confidence: 99%
“…The study of covert networks has received high levels of attention from the modeling community in the last decade. Among others, covert networks have been formally characterized by Tsvetovat and Carley (2005), McAllister (2004) and McCormick and Owen (2000), and their optimal network structures have been analyzed and approximated by Lindelauf et al (2009a) and Enders and Su (2007). Other approaches concern covert network destabilization strategies, see Farley (2003) and Carley et al (2003), and tools to identify the most important members of the corresponding organizations, see Koschade (2006), Magouirk and Sageman (2008) and Sparrow (1991).…”
Section: Introductionmentioning
confidence: 99%